See you again! (2014)
Dedicated to my daughter Daniela!I wake up as I do every day and every time. I still have the bitter taste that insomnia usually leaves me. I always have something to think about, be it the daily grind of everyday life, or maybe, how I would like everything to change, and at the end of the day, to achieve everything I have ever wanted.